Handbook of surface and interface analysis methods for problem-solving - Rivière, J. C.; Myhra, S. (Sverre) 1943- (Marcel Dekker, 1998)
Integrating advances in instrumentation and methods, this work offers an approach to solving problems in surface and interface analysis, beginning with a particular problem and then explaining the most rational and efficient route to a solution. The book discusses electron optical and scanned probe microscopy, high spatial resolution imaging and synchrotron-based techniques. It emphasizes problem-solving for different classes of materials and material function.